THE CORRELATION OF PHYSICAL ACTIVITY IN REDUCING SYMPTOMS OF PREMENSTRUAL SYNDROME (PMS) AMONG GIRLS IN PRIVATE SENIOR HIGH SCHOOL OF ABULYATAMA, KUTA BARO, ACEH BESAR - Nora Mirda; Khaira Rizki; Ellyza Fazlylawati (PT. Jurnal Center Indonesia Publisher, 2025)
Premenstrual Syndrome (PMS) includes physical, emotional, and behavioral symptoms pre-menstruation. These symptoms affect the daily activities of adolescent girls. Regular physical activity can increase endorphin production, which may reduce PMS symptoms. This study aims to investigate the correlation between physical activity and PMS symptoms among girls in Abulyatama Senior High School. This study used a quantitative technique with a descriptive approach. The population consisted of all 41 adolescent girls at Abulyatama Senior High School who were also selected as the sample using a total sampling technique. The data collection from April 24th to May 5th, 2025. The Global Physical Activity Questionnaire (GPAQ) was used to measure physical activity level, while the Shortened Premenstrual Assessment Form (SPAF) was used to assess PMS symptoms. Data analysis used the Chi- Square test using univariate and bivariate analysis techniques. The results showed a correlation between physical activity and premenstrual syndrome with p = 0.018 correlation (p<0,05). These findings suggest there is a significant correlation between physical activity and reduced PMS symptoms among girls in Abulyatama Senior High School. This study suggests that the girls regularly do physical activity and use it as one non-pharmacological treatment to reduce PMS symptoms.